Effect of growth rate from birth through thirty months on performance of heifers - Schalles, R.R.; Fleck, A.T.; Kiracofe, G.H.; Corah, L.R. (Kansas State University. Agricultural Experiment Station, 2011)
Heifers with faster gain the first and second winter (weaning to yearling and 18 months to 2 years old) had better production and reproduction than heifers with low or moderate gains. Gains during the first winter (weaning to yearling) had more influence on future performance than gains during the second winter as bred heifers.
Keywords: Beef; Growth rate; Performance; Heifers; Gains